#### Answer

$7x$

#### Work Step by Step

$6x^2+3x-(6x^2-4x)=(6x^2-6x^2)+(3x-(-4x))=7x$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$7x$

$6x^2+3x-(6x^2-4x)=(6x^2-6x^2)+(3x-(-4x))=7x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.